Characterization of regulation and expression patterns of Escherichia coli Hsp31 protein - Mujacic, Mirna (My University, 2006)
Escherichia coli is exposed to a variety of environmental stresses in its natural habitats. On a cellular level, these stresses wreak havoc by disrupting the structure and function of proteins, which ultimately leads to a breakdown of finely tuned and complex cellular machineries. To cope with constant environmental onslaughts, Escherichia coli employs an elaborate system of protein networks whose primary role is to prevent and alleviate stress-inflicted damaged. Although many components of its various stress response systems are known, the genome of Escherichia coli is still strewn with open reading frames whose cellular roles remain elusive. One such open reading frame, named hchA, codes for Hsp31, a homodimeric protein with structural similarities to archaebacterial PfpI-type peptidases and human DJ-1 protein, which has been implicated in early onset Parkinson's disease. hchA was initially identified in an analysis of Escherichia coli's transcriptome as one of 23 genes of unknown function whose expression is thermally induced. In vitro studies have shown that under heat shock conditions Hsp31 functions as a molecular chaperone - a type of a stress protein whose role is to help proteins reach their proper folded form - by capturing partially folded proteins and releasing them in an active form once the thermal stress has abated. To investigate the role of Hsp31 under physiological conditions, we studied its regulation and expression patterns. We have found that Hsp31 is a bona fide heat shock protein whose heat-induced expression is regulated by the housekeeping sigma factor sigmaD and the global gene silencer H-NS. Its absence under severe heat shock conditions greatly impairs cell survival and leads to a decrease in protein integrity of a subset of cellular proteins. Moreover, its expression is induced under a variety of stress conditions, while its absence under such conditions leads to an increase in protein aggregation. Hsp31 also accumulates in the stationary phase of growth through the action of the stationary phase sigma factor sigma S. Consequentially, stationary phase DeltahchA cells exhibit a decrease in fitness when exposed to a number of stress stimuli, with a greatly diminished survival in the presence of severe acidic stress.
Thesis (Ph. D.)--University of Washington, 2006.
Keywords: Theses--Bioengineering